Effect of mounting brackets on thermal performance of buildings with ventilated facades. (July 2019) - Nowak, Katarzyna; Byrdy, Aleksander
Ventilated facades systems have become a widely used solution for elevations of commercial buildings. Yet, those systems use metal frames and brackets that interrupt continuity of thermal insulation by creating point thermal bridges. The influence of anchorage systems on the total performance of walls is either neglected or simplified upon assumption that their influence is not important because the thermal insulation is thick enough. This article, based on three-dimensional analyses, demonstrates a significant impact of point bridges created by the anchorage systems of ventilated building facades on the heat loss. The results emphasize the need for individual calculations.